Answer:
1) Solving the term
using F.O.I.L we get ![\mathbf{6x^2+x-15}](https://tex.z-dn.net/?f=%5Cmathbf%7B6x%5E2%2Bx-15%7D)
2) solving the term
using F.O.I.L we get ![\mathbf{x^2-11x-26}](https://tex.z-dn.net/?f=%5Cmathbf%7Bx%5E2-11x-26%7D)
3) Solving
using square of binomial we get ![\mathbf{x^2+10x+25}](https://tex.z-dn.net/?f=%5Cmathbf%7Bx%5E2%2B10x%2B25%7D)
4) Solving
using square of binomial we get ![\mathbf{x^2-6x+9}](https://tex.z-dn.net/?f=%5Cmathbf%7Bx%5E2-6x%2B9%7D)
Step-by-step explanation:
1) (3x + 5)(2x - 3). Solve using the F.O.I.L.
F.O.I.L stands for First, Outer Inner Last
We have ![(3x + 5)(2x - 3)](https://tex.z-dn.net/?f=%283x%20%2B%205%29%282x%20-%203%29)
First: 3x(2x)
Outer: 3x(-3)
Inner: 5(2x)
Last: 5(-3)
Solving we get:
![(3x + 5)(2x - 3)\\=3x(2x)+3x(-3)+5(2x)+5(-3)\\=6x^2-9x+10x-15\\=6x^2+x-15](https://tex.z-dn.net/?f=%283x%20%2B%205%29%282x%20-%203%29%5C%5C%3D3x%282x%29%2B3x%28-3%29%2B5%282x%29%2B5%28-3%29%5C%5C%3D6x%5E2-9x%2B10x-15%5C%5C%3D6x%5E2%2Bx-15)
So, solving the term
using F.O.I.L we get ![\mathbf{6x^2+x-15}](https://tex.z-dn.net/?f=%5Cmathbf%7B6x%5E2%2Bx-15%7D)
2) (x + 2)(x – 13). Solve using the F.O.I.L.
F.O.I.L stands for First, Outer Inner Last
We have ![(x + 2)(x -13)](https://tex.z-dn.net/?f=%28x%20%2B%202%29%28x%20-13%29)
First: x(x)
Outer: x(-13)
Inner: 2(x)
Last: 2(-13)
Solving we get:
![(x + 2)(x - 13)\\=x(x)+x(-13)+2(x)+2(-13)\\=x^2-13x+2x-26\\=x^2-11x-26](https://tex.z-dn.net/?f=%28x%20%2B%202%29%28x%20-%2013%29%5C%5C%3Dx%28x%29%2Bx%28-13%29%2B2%28x%29%2B2%28-13%29%5C%5C%3Dx%5E2-13x%2B2x-26%5C%5C%3Dx%5E2-11x-26)
So, solving the term
using F.O.I.L we get ![\mathbf{x^2-11x-26}](https://tex.z-dn.net/?f=%5Cmathbf%7Bx%5E2-11x-26%7D)
3) (x + 5)^2. Solve using the square of Binomial.
The square of binomial is: ![(a+b)^2=a^2+2ab+b^2](https://tex.z-dn.net/?f=%28a%2Bb%29%5E2%3Da%5E2%2B2ab%2Bb%5E2)
Solving:
![(x+5)^2\\=(x)^2+2(x)(5)+(5)^2\\=x^2+10x+25](https://tex.z-dn.net/?f=%28x%2B5%29%5E2%5C%5C%3D%28x%29%5E2%2B2%28x%29%285%29%2B%285%29%5E2%5C%5C%3Dx%5E2%2B10x%2B25)
So, solving
using square of binomial we get ![\mathbf{x^2+10x+25}](https://tex.z-dn.net/?f=%5Cmathbf%7Bx%5E2%2B10x%2B25%7D)
4) (x -3)^2. Solve using the square of Binomial.
The square of binomial used is: ![(a-b)^2=a^2-2ab+b^2](https://tex.z-dn.net/?f=%28a-b%29%5E2%3Da%5E2-2ab%2Bb%5E2)
Solving:
![(x-3)^2\\=(x)^2-2(x)(3)+(3)^2\\=x^2-6x+9](https://tex.z-dn.net/?f=%28x-3%29%5E2%5C%5C%3D%28x%29%5E2-2%28x%29%283%29%2B%283%29%5E2%5C%5C%3Dx%5E2-6x%2B9)
So, solving
using square of binomial we get ![\mathbf{x^2-6x+9}](https://tex.z-dn.net/?f=%5Cmathbf%7Bx%5E2-6x%2B9%7D)